Enhancing Vocabulary Mastery through Applying Visual Auditory Kinesthetic (VAK): A Classroom Action - Heri Hidayatullah; Sirojil Munir; Tawali Tawali (Journal of Language and Literature Studies, 2022)
Vocabulary mastery is paramount to support the four language skills and it determines the success of students’ communication after grammatical competences. lexical competence is assumed as the second competence to that of the grammar. One of the alternatives in teaching vocabulary is visual auditory kinesthetic (VAK). This classroom action research (CAR) aimed at applying the VAK due to the students’ difficulties in memorizing new vocabulary especially the abstract noun. The procedure of the CAR comprises planning, acting, observing, and reflecting. Each stage has activities to attain the research goals. The subjects of this study were the Seventh Graders of SMP Islam Al-Badriyah. There were a  vocabulary test, questionnaire, and observation sheet as the research instruments. Then, the data was analyzed using both quantitatively and qualitatively. The findings from the vocabulary test showed that 21 out of 25 students passed the settled minimum criteria or the mean score fell on 77. It found out the students were active participation, paid good attention to the material and showed enthusiasm in the English class. It can be concluded that the application of the VAK could increase not only the students’ vocabulary mastery but also classroom participation. In addition, the result of this current study proved that the application of VAK as one of the teaching alternatives could lead the students in memorizing abstracted vocabularies.